Stabilizacja makroekonomiczna w Polsce a kryteria uczestnictwa w strefie euro - Pawłowski, Grzegorz (Macroeconomic Stabilization in Poland and Criterions of Participation in Euro Area, 2009)
Polish economic policy often has a short-run perspective. In order to establish long-run development, economic policy needs the strategic dimension. In the 2009 Polish economic system is still not balanced. In the strategic perspective Polish economic policy shall focus on criterions of convergence, but it will stress the role of the general macroeconomic stabilization too. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 292-299